PH-Responsive Cy5 dyes having nucleophilic substituents for molecular imaging. Issue 35 (29th August 2018) - Oe, Masahiro; Miki, Koji; Mu, Huiying; Harada, Hiroshi; Morinibu, Akiyo; Ohe, Kouichi
Graphical abstract: Highlights: Facile synthesis of pH-responsive Cy5 dyes. Dyes responding in various pH ranges. Structural changes in response to acidic compartments of cells. Abstract: pH-Responsive fluorescent pentamethine cyanine (Cy5) derivatives having nucleophilic substituents were synthesized. Cy5 derivatives1-O having mercaptopropyl, hydroxypropyl, and aminopropyl groups on an indole nitrogen atom showed pH-dependent equilibria between a fluorescent open-ring structure (1-O ) and a non-fluorescent closed-ring structure (1-C ) in pH ranges 3–7, 6–7.5, and 8–9, respectively. pH-Responsive dyes1a-C having a 1, 3-thiazinane structure were easily internalized into A549 cells and converted to open-ring structure1a-O in response to the relatively low pH of acidic compartments in the cells.